Il presidente Schreber e il signor K. Dinamiche di transfert nella psicoterapia di gruppo - Roccioletti, Gioia; Masillo, Alice; Salvador, Enrica (Il sogno della farfalla, 2008)
The hypothesis of this research is that both the paranoiac and the depressive dispositions originate from the dynamics of interpersonal relationships and cannot be considered innate within the psychosocial development of people, as psychoanalysis suggests in theories such as the Freudian one on primary narcissism that constitutes the precedent to the formulation of the schizoparanoid position (Klein), the delusion of omnipotence in the process of individuation (Mahler), the exhibitionist and megalomaniac ego (Kohut). The schizoparanoid and depressive positions should therefore be seen, at a clinical level, as pathological reactions within a relationship of transference and counter-transference. A decisive moment in psychotherapy is the passage in the patient from a paranoiac thought to a depressive ideation: the interpretation of the annulment drive puts an end to the delusion of omnipotence which would make the therapist non-existent rendering him/her a persecutory object thus allowing the patient to withdraw his/her projective identification that deforms the internal reality of the psychiatrist. On the other hand, the psychiatrist must have the certainty of his/her interpretations on which to base the rejectionand frustration of the negation. This certainty, which is completely different from the absolute belief typical of the delusional state which annuls the internal image of the other, bases itself on a human identity which goes beyond rationality and the conscious dimension and is capable of creating a dialectical relationship with the patient to bring about a transformation.